PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINANTERHADAP KEPUASAN KERJA (STUDI DI RUMAH SAKIT MUHAMMADIYAH METRO) - Ali, Karnila; Agustian, Didiek Wijaya (Jurnal Manajemen Magister Darmajaya, 2018)
The medical services industry is now increasingly competitive. This encourages hospital hospitals to further improve their performance. The Muhammadiyah Metro Hospital is no exception. One effort that can be done is to improve employee performance by increasing job satisfaction. The problem in this study is to find out whether the influence of organizational culture and leadership style on job satisfaction to improve employee performance at Muhammadiyah Metro Hospital. This study aims to determine whether the influence of organizational culture and leadership style on job satisfaction to improve employee performance at Muhammadiyah Metro Hospital. This study used a sample of 93 employees from a population of 170 employees. This study uses the SEM (Structural Equestion Modeling) method. From the results of the tests that have been made it is known that (1). organizational culture has a positive and significant effect on job satisfaction and employee performance, (2). leadership style does not have a positive and significant effect on job satisfaction, but has a positive and significant effect on employee performance, (3). Job satisfaction does not have a positive and significant effect on employee performance.Keywords — Organizational Culture, Leadership Style, Job Satisfaction and Employee Performance.